Analisis Potensi Minawisata Dikawasan Pesisir Desa Bondalem Buleleng Bali - Dewi Wulandari; I Nyoman Dodik Prasetia; Made Dwipa Kusuma Maharani; Jasmine Masyitah Amelia; Gressty Sari Br Sitepu; Bambang Sutikno; Abdul Wafi (Samakia : Jurnal Ilmu Perikanan, 2024)
Geographically, Buleleng Regency in North Bali has high potential coastal resources, with a coastline length reaching 157.05 km. Bondalem Village is in Tejakula District, Buleleng Regency, in the northern part of the Island of the Gods. The condition of the coral reefs in the Bondalem Waters area is categorized as very good, with coral reef cover percentages ranging from 65.93% to 81.33%. Besides having potential for diving tourism, Bondalem Village also boasts cultural attractions and local artistic wisdom. The purpose of this research is to identify the minatourism potential in Bondalem Village from the social aspect of the community. This research uses a descriptive quantitative method. The research process begins with the preparation of a proposal and the drafting of a questionnaire, followed by data collection, data processing, and data testing before drawing conclusions from the research activities. Based on research conducted on the potential of minatourism from the social aspect of the community in Bondalem Village, Buleleng, Bali, it is concluded that Bondalem Village in North Bali, specifically in Buleleng Regency, has minatourism potential that can be developed based on cultural, economic, and environmental assessments. The analysis of cultural, economic, and environmental aspects influencing minatourism potential, based on interviews with respondents, yielded scores of 3.253, 3.256, and 3.220, respectively, indicating that respondents support the development of minatourism potential in Bondalem Village from these aspects. This research is expected to provide useful input for various parties, especially the government, the Bondalem Village authorities, and researchers, to jointly support sustainable minatourism development.